Considering bills of material in hybrid flow shop scheduling problems - Botta-Genoulaz, V. (1997 IEEE International Symposium on Assembly and Task Planning (ISATP'97) : towards flexible and agile assembly and manufacturing, August 7-9, 1997, Marina del Rey Hotel, Marina del Rey, California, 1997)
In this paper, we propose to take bills of material into account in hybrid flow shop scheduling problems. We study the scheduling of N jobs in a hybrid flow shop with V-stages and identical parallel machines. We also consider that the jobs are subject to precedence constraints. Job-precedence constraints enable the modeling of different processing units in a flow shop organization and also the modeling of bill of material aspects. Six heuristics are presented to solve this problem using the minimum makespan criterion. Numerous experiments have been undertaken to assess the performance and robustness of these new heuristics and the computational results illustrate the quality of the solution obtained.